Modification of Multi-Attribute Utility Theory in Determining Scholarship Recipient Students - Arshad, Muhammad Waqas; Setiawansyah, Setiawansyah; Rahmanto, Yuri; Palupiningsih, Pritasari; Maryana, Sufiatul (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
Educational scholarships are financial aid given to students or students to support the financing of their education. Mistakes in the assessment of scholarship recipients are often related to subjectivity and lack of transparency in the selection process. Unclear or inconsistent assessment criteria can lead to unfairness, where some deserving candidates may not get the same opportunities. The number of data used in Determining Scholarship Recipient Students is 10 students. The purpose of the MAUT modification research with geometric mean in producing criterion weights is to improve accuracy, stability, and consistency in the decision-making process. This study also aims to test the effectiveness of the geometric mean method in producing more objective and structured weights, as well as compare it with other traditional MAUT methods such as direct addition or multiplication. The modification of the MAUT method with a geometric mean is named G-MAUT. The results of the ranking of scholarship recipients using the G-MAUT method the first-place scholarship recipient with a final score of 1.0048 was obtained by Student 3, the second-place scholarship recipient with a final score of 0.6260 was obtained by Student 8, and the third-place scholarship recipient with a final score of 0.5048 was obtained by Student 5. This modification under the name G-MAUT allows for a more holistic and comprehensive assessment of potential recipients, ensuring that non-academic aspects are also taken into account proportionately.